2022
DOI: 10.1128/spectrum.00735-22
|View full text |Cite
|
Sign up to set email alerts
|

Host Age Prediction from Fecal Microbiota Composition in Male C57BL/6J Mice

Abstract: The gut microbiome of a host changes with age. Cross-sectional studies demonstrate that microbiota of different age groups are distinct but do not demonstrate the temporal change that a longitudinal study is able to show. Here, we performed a longitudinal study of adult mice for over 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
1
8
1
Order By: Relevance
“…Further, regardless of sex, aged mice had lower relative abundance of A. municiphila, an important microbe known to be associated with gut health (Xu et al, 2020). In support of these findings, a recent publication in C57BL/6J males across lifespan was also shown to have an age-associated loss of A. municiphila (Low et al, 2022). Our results demonstrate many differences in the microbiome were also associated sex, with more pronounced sex-specific differences in the aged population.…”
Section: Discussionsupporting
confidence: 85%
“…Further, regardless of sex, aged mice had lower relative abundance of A. municiphila, an important microbe known to be associated with gut health (Xu et al, 2020). In support of these findings, a recent publication in C57BL/6J males across lifespan was also shown to have an age-associated loss of A. municiphila (Low et al, 2022). Our results demonstrate many differences in the microbiome were also associated sex, with more pronounced sex-specific differences in the aged population.…”
Section: Discussionsupporting
confidence: 85%
“…We showed that Tmu induces longitudinal shifts in bacterial composition and increases abundance and activity of Helicobacter spp., consistent with previous trichomonad studies [ 15 , 80 ]. Although previous studies have shown natural microbiome variation in mice over their lifespan [ 81 ], our metatranscriptomic data in particular suggest little change over the 28 days of the experiment. As mice were co-housed prior to protist exposure to normalize their microbiomes, the similarity of 16S rRNA compositions in day 28 control mice to day 0 preinfection samples, relative to the large Tmu -driven shift in the colonized mice, further supports limited variation during this period.…”
Section: Discussioncontrasting
confidence: 66%
“…We found no significant separation in the laryngeal microbiota (i.e., no significant differences in post-hoc analyses of beta-diversity) across age groups. Although the gut microbiota has been shown to vary throughout the lifespan [ 52 ], similar result has not been reported in the laryngeal microbiome. Lastly, while the selection of age group is based on prior research [ 27 ], it is possible that the age groups may not accurately reflect microbial variation across aging.…”
Section: Discussionmentioning
confidence: 79%